PENGARUH VARIASI KECEPATAN PUTARAN RODA DAN BAHAN KAMPAS TERHADAP TEMPERATUR OPERASIONAL REM CAKRAM : EFFECT OF WHEEL ROTATION SPEED VARIATIONS AND PAD MATERIAL ON THE OPERATIONAL TEMPERATURE OF DISC BRAKE - Dias Muhammad Zaidaan Rizky; Eko Yudiyanto (Jurnal Teknik Mesin, 2026)
This study investigates the influence of wheel rotational speed and brake pad material on the temperature of disc braking systems. The experimental setup incorporates an LM393 speed sensor and a MAX6675 thermocouple temperature sensor, both interfaced with an Arduino microcontroller, with data output displayed via a MATLAB GUI and an LCD screen. Testing was conducted in three repetitions across four rotational speed variations (1000, 1500, 2000, and 2500 rpm) and three types of brake pad materials: standard, semi-metallic, and full-metallic. The results indicate a direct correlation between rotational speed and braking temperature. At 2500 rpm, the highest temperatures recorded were 83.3°C for full-metallic pads, 59°C for semi-metallic pads, and 47°C for standard pads. These findings confirm that both the pad material and wheel speed significantly affect the heat generation during braking.